The Effect of Using English Slang Words on Students’ Speaking Skill Of The Year 2018/2019 Tenth Grade Students Of Sma Negeri 1 Hinai Kabupaten Langkat - Nudia Yultisa; Ainun Mardiah (STKIP Budidaya Binjai, 2018)
This study aimed to find out whether using English Slang Words affects students’ speaking skill of the 2018/2019 tenth grade students of SMA Negeri 1 Hinai Kabupaten Langkat. In this study, using English slang words as the independent variable (X) and students’ speaking skill as the dependent variable (Y), with the hypothesis: using English slang words significantly affects students’ speaking skill of the 2018/2019 tenth grade students of SMA Negeri 1 Hinai Kabupaten Langkat . The population of this study was the 2018/2019 tenth grade students of SMA Negeri 1 Hinai Kabupaten Langkat. Which consisted of 154 students. The sample was taken buy using cluster random sampling, that consist of 81 students. Then, the sample was divided into two groups, the group taught by using English slang words was as the experimental group and the group taught without Englih slang words was as the control group. The writer used interview test as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table, (tobserved = 7,47 > ttable = 2,00). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using English Slang Words significantly affects the students’ speaking skill of the 2018/2019 tenth grade students of SMA Negeri 1 Hinai Kabupaten Langkat.Keywords: English slang words, speaking skill